MAX-Sense - Khazen, Georges (2005)
In this paper we are proposing a new distributed system architecture to address the problem of very large scale sensor network monitoring. By dynamically aggregating and processing data from sensor networks, databases and other sources, the system can detect hazardous patterns soon enough to prevent serious human damage. The system involves discovering and studying the underlying network topology then dispatching mobile agents (MA) for collection, analysis, and processing of data that is packed in XML format. This paper describes the architecture and its elements, including the employed mobile agents, which are designed to respond to different levels of sensed security threats in a timely manner. We also present a prototype system implementation that was developed to test the performance of the developed architecture.